Social Assistance and Labor Market Programs in Latin America : Methodology and Key Findings from the Social Protection Database - Cerutti, Paula (World Bank, Washington, DC, 2014)
How much do countries spend on social protection? Do social protection programs cover all poor people? And, how well are they targeted? It is notoriously hard to find comprehensive cross-country data on social protection programs which can help answer such questions and allow to benchmark social protection systems. The World Bank s Latin American and Caribbean (LAC) Social Protection Database attempts to fill these knowledge gaps by collecting and systematizing data on social protection programs from both administrative sources and household surveys. The data assembled provides a powerful tool to study trends and analyze program performance as well as benchmark countries social protection systems. We found both expected and unexpected trends in spending on social protection and coverage of social protection programs across countries. Between 2000 and 2010 expenditure on social assistance nearly tripled. At a program level, conditional cash transfer programs ceased to dominate social assistance spending, with the exception of Mexico, and have come second to social pension spending in Brazil, Uruguay and Chile. Labor market programs remain small and fragmented, but show much more counter-cyclical patterns.